PEMIKIRAN NEO-MODERNISME NURCHOLISH MADJID–K.H. ABDURRAHMAN WAHID: Memahami perkembangan pemikiran intelektual islam - Hamidah Hamidah (MIQOT: Jurnal Ilmu-ilmu Keislaman, 2011)
Abstract: Nurcholish Madjid and K.H. Abdurrahman Wahid’s Neo- Modernism: Understanding the Development of Islamic Intellectual Thought. Since the 1970s Islamic thought in Indonesia has witnessed significant dynamics of development. Two of the prominent Muslim thinkers of this era are Nurcholish Madjid dan K.H. Abdurrahman Wahid both of which are commonly categorized as the thinker of Neo-modernism. Nurcholish developed such concepts as “Islam Yes, Partai Islam No!,” secularization, and secularism whereas Abdurrahman Wahid introduced such ideas as indigenization of Islam, pluralism and protection for the minority group. The author argues that both thinkers converged in the idea of making Islam as a cultural force that should be workable in whole process of nation and statehood. In this article, the author studies various aspects of Neo- modernism in the thoughts of Cak Nur and Gus Dur, as they are popularly called respectively, and analyzes the extent to which the social, cultural and religious aspects influenced their thoughts.Kata Kunci: Neo-Modernisme, Nurcholish Madjid, Abdurrahman Wahid, Islam Indonesia